Sociolinguistics - Mullen, Alex (Oxford University Press, 2016)
This chapter begins by considering the motivations for undertaking sociolinguistic studies and discusses the range and quality of evidence that can be marshalled for early Britain. The pre-Roman linguistic situation and the advent and spread of Latin are assessed using linguistic and archaeological evidence, and the extent and nature of Latin–Celtic bilingualism across time, space, and social levels explored. A presentation of the long-standing debate on the nature of Latin spoken in Roman Britain follows, and new evidence is offered to counter the traditional view that British Latin was particularly conservative. The chapter closes by looking at the legacy of the linguistic impact of Roman Britain, briefly considering the post-Roman inscriptions and language contact phenomena in the Germanic languages.